(untitled) (Research, Society and Development, 2022)
HIV is the human immunodeficiency virus that causes AIDS, acquired immunodeficiency syndrome, and after its evolution and high rate of cases in the world, Kaposi’s Sarcoma was present concomitantly with these patients, which is a disease that affects the lymphatic vessels, and that can reach from the oral cavity to other and various organs. Therefore, the present work is an integrative, descriptive-explanatory review of a basic nature on the relationship between the high incidence of Kaposi’s sarcoma in HIV-seropositive patients. Thus, the work aims to describe the mechanisms of HIV in terms of its defense cells and TCD4+ variation, the role of HHV-8 in the disease and also the action of antiretroviral therapy in this context. Furthermore, to analyze the interaction of the aforementioned mechanisms for the conclusion of the etiology and, in addition, the analysis of the treatment and prognosis of the disease.